Colonoscopy sedation: clinical trial comparing propofol and fentanyl with or without midazolam - Jose Francisco Nunes Pereira das Neves; Mariana Moraes Pereira das Neves Araújo; Fernando de Paiva Araújo; Clarice Martins Ferreira; Fabiana Baeta Neves Duarte; Fabio Heleno Pace; Laura Cotta Ornellas; Todd H. Baron; Lincoln Eduardo Villela Vieira de Castro Ferreira (Brazilian Journal of Anesthesiology, 2016)
Colonoscopy is one of the most common procedures. Sedation and analgesia decrease anxiety and discomfort and minimize risks. Therefore, patients prefer to be sedated when undergoing examination, although the best combination of drugs has not been determined. The combination of opioids and benzodiazepines is used to relieve the patient's pain and discomfort. More recently, propofol has assumed a prominent position. This randomized prospective study is unique in medical literature that specifically compared the use of propofol and fentanyl with or without midazolam for colonoscopy sedation performed by anesthesiologists. The aim of this study was to evaluate the side effects of sedation, discharge conditions, quality of sedation, and propofol consumption during colonoscopy, with or without midazolam as preanesthetic. The study involved 140 patients who underwent colonoscopy at the University Hospital of the Federal University of Juiz de Fora. Patients were divided into two groups: Group I received intravenous midazolam as preanesthetic 5 min before sedation, followed by fentanyl and propofol; Group II received intravenous anesthesia with fentanyl and propofol. Patients in Group II had a higher incidence of reaction (motor or verbal) to the colonoscope introduction, bradycardia, hypotension, and increased propofol consumption. Patient satisfaction was higher in Group I. According to the methodology used, the combination of midazolam, fentanyl, and propofol for colonoscopy sedation reduces propofol consumption and provides greater patient satisfaction. Resumo: A colonoscopia é um dos procedimentos mais feitos. Sedação e analgesia diminuem a ansiedade e o desconforto e minimizam riscos. Em razão disso, os pacientes preferem que o exame seja feito sob anestesia, embora não tenha sido determinada a melhor combinação de fármacos. A associação de benzodiazepínicos com opioides é usada para aliviar a dor e o desconforto do paciente. Mais recentemente, o propofol assumiu posição de destaque. Este estudo, prospectivo e randomizado, é único na literatura médica e especificamente comparou o uso do propofol e fentanil associado ou não ao midazolam na sedação para colonoscopia feita por anestesiologistas. Os objetivos do estudo foram avaliar os efeitos colaterais da sedação, as condições de alta, a qualidade da sedação e o consumo de propofol durante a colonoscopia, com ou sem o midazolam como pré-anestésico. Envolveu 140 pacientes submetidos à colonoscopia, no Hospital Universitário da Universidade Federal de Juiz de Fora. Os pacientes foram divididos em dois grupos. O Grupo I recebeu, por via endovenosa, midazolam como pré-anestésico, cinco minutos antes da sedação, seguido do fentanil e propofol. O Grupo II recebeu, por via endovenosa, anestesia com fentanil e propofol. Os pacientes do Grupo II apresentaram maior incidência de reação (motora ou verbal) à introdução do colonoscópio, bradicardia, hipotensão arterial e maior consumo de propofol. A satisfação dos pacientes foi maior no Grupo I. De acordo com a metodologia empregada, a associação de midazolam ao propofol e fentanil para sedação em colonoscopia reduz o consumo de propofol e cursa com maior satisfação do paciente. Keywords: Sedation, Colonoscopy, Propofol, Fentanil, Midazolam, Palavras-chave: Sedação, Colonoscopia, Propofol, Fentanil, Midazolam